Market Reaction to Voluntary and Mandatory Announcements of Independent Director Appointments - Lin, Hueh-Chen; Huang, Chin-Sheng; Yang, Jack J. W. (International Journal of Economics and Financial Issues, 2014)
In this paper, we use a unique natural experimental setting to examine the market value of both voluntary and mandatory independent director appointments using a sample of Taiwanese listed firms. We find a significantly positive stock price reaction when a firm announces it is appointing independent directors to its board. Particularly, poor corporate performance and a higher degree of information asymmetry significantly benefit from the mandatory appointment. We conclude that the mandatory regulation for Taiwan listed firms to have a minimum number and ratio of independent directors on their boards appears to be a sound policy. Keywords: Corporate Governance; Board Independence; Independent Director; Mandatory Appointment. JEL Classifications: G34; G38